Asymmetric taxation, limited liability, and agency conflicts. (June 2021) - Schneider, Georg; Scholze, Andreas; Meißner, Fabian
Abstract: Current income tax systems are characterized by an asymmetric treatment of gains and losses. This implies that the (effective) tax rate on profits exceeds that on losses. We study the contractural relationship between two parties (the principal and the agent). For example, such a relationship occurs if a franchisee (agent) contracts with a franchiser (principal) or when a new partner (agent) enters a partnership (principal). We focus on the effect of the agent's asymmetric taxation on the principal's optimal contract and show that the principal's expected profit is a non-monotonous function of the agent's loss tax rate. In particular, we show that the principal can be strictly better off if the agent is taxed more heavily. This result stands in contrast to the existing literature, which has only shown that lower taxation at the agent's level increases the principal's expected profit.